University students' knowledge, self-efficacy, outcome expectations, and barriers related to reducing sedentary behavior: a qualitative study. Issue 4 (19th May 2022) - Pachu, Navjot; Strachan, Shaelyn; McMillan, Diana; Ripat, Jacquie; Webber, Sandra
Abstract: Objective To explore university students' knowledge, self-efficacy, outcome expectations, barriers and ideas related to reducing sedentary behavior using a qualitative approach. Participants: Nineteen students from a Canadian university participated. Methods: Four focus groups were conducted. Discussions were recorded, transcribed, and coded to identify categories and themes. Results: Some students lacked knowledge of the concept, but most were generally aware of health risks associated with sedentary behavior. Most students were confident they could reduce sedentary behavior, but felt it would be unlikely they would actually do so because: (a) it is not a priority, (b) the health consequences are distal, (c) increasing standing and light-intensity activity would not provide meaningful health benefits, and (d) class schedules/norms/infrastructure encourage sitting and are not under their control to change. Conclusion: Findings from this study may help inform intervention strategies aimed at decreasing excessive sedentary behavior among university students.